Identification of Determinant Factors In House Selection at PT Tiga Hasta Gemilang - Thoriq Cholili; Ahmad Ikhwan Setiawan (Green Publisher Indonesia, 2025)
The growth of urbanization and increasing housing demand require developers such as PT Tiga Hasta Gemilang to better understand consumer preferences. This study aims to identify the determining factors influencing consumer decisions in house selection, group these factors through factor analysis, and determine the dominant factor affecting purchase decisions. A quantitative survey approach was employed using structured questionnaires, with data analyzed through Exploratory Factor Analysis (EFA) involving KMO tests, Total Variance Explained, and Rotated Component Matrix. The findings reveal ten main factors influencing house selection: financial affordability, financing support, digitalization and promotion, property investment, location and accessibility, environment and public facilities, physical specifications, developer credibility, services and information, and socio-cultural aspects. The dominant factor is financial affordability, which contributes the largest variance. These results highlight that house purchase decisions are multidimensional, yet financial considerations remain the primary determinant. In conclusion, developers should focus on flexible financing schemes, legal transparency, construction quality, and interactive digital promotion strategies to strengthen consumer trust and market competitiveness.